The Design of a Low Power MEMS Based Micro-hotplate Device Using a Novel Nickel Alloy for Gas Sensing Applications - Bijoy Kantha; Subir Kumar Sarkar (Журнал нано- та електронної фізики)
In this paper comparative analysis of MEMS (Micro-electro-mechanical System) based Micro-hotplate using three different heating elements use as separately are presented. Three different materials (viz. DilverP1, Polysilicon, and Platinum) are used as heating elements with same thickness of 0.2 µm. CoventorWareTM simulator has been used for construction of 3D model and electro-thermo-mechanical analysis of Micro-hotplate device. Power consumption, stress and displacement of Micro-hotplate are studied at operating temperature (165 ºC). It is obtained that power consumption, stress and displacement of Dilverp1 heating element are 13.06 mW, 190 MPa and 0.028 µm which are less in comparison to those with Poly Silicon heater and Platinum heater at moderate temperature (150-200 °C) over the sensing material (ZnO).